A Study on the Recurrence Rate of Trigeminal Neuralgia after MVD and the Related Factors - Zheng, Jiang-Hua; Sun, Kai; Zhang, Hai-Tao; Xie, Yun-Jie; Wang-Yang, Ling-Xi; Chen, Hao-Yang; Wang, Chong (Journal of Neurological Surgery Part B: Skull Base, 2019)
The aim of this article is to investigate the related factors affecting the recurrence of microvascular decompression (MVD) after trigeminal neuralgia. We selected 400 cases of patients who met the diagnostic criteria of primary trigeminal neuralgia. The recurrence rate of patients and their statistical data related factors such as age, gender, disease duration, pain branches, vascular compression, patients, and complications (urban and rural), were collected. Of the 400 cases, 36 had recurrence after 2 years. In female group, the recurrence rate was (9.4%) higher than the recurrence rate in male group (8%); no recurrence rate of vascular compression group (40%) was higher than that of vascular compression group recurrence rate (8.6%); the recurrence rate of each branch in pain group from high to low was V2–3 (13.4%), V2 (12.5%), V1 (9.1%), V3 (7.5%), V1–2-3 (4.4%), V1–2 (4.3%), V1–3 (0%); and the difference was statistically significant (p < 0.05).Gender of the patient, the presence of vascular pressure, and the branch of pain could significantly affect the postoperative recurrence rate of trigeminal neuralgia in patients treated with simple MVD (p < 0.05).
Keywords: trigeminal neuralgia; microvascular decompression; pain branch; recurrence rate